2017
DOI: 10.1002/bjs.10316
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and clinical implications of chyle leak after pancreatic surgery

Abstract: Chyle leak is a relevant complication, with an incidence of more than 10 per cent after pancreatic surgery, and has a major impact on hospital stay. Drainage volume is associated with hospital stay and success of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 18 publications
0
53
3
Order By: Relevance
“…These structures may be injured during pancreaticoduodenectomy (PD), resulting in chyle leakage, which is a well‐known but poorly characterized complication of PD . This chyle leakage often presents as milky‐appearing drainage outflow, with a triglyceride content >110 mg/dL and usually becomes evident once oral or enteral feeding resumes after surgery . Chyle leakage might induce malnutrition and lead to an immune‐compromised state .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These structures may be injured during pancreaticoduodenectomy (PD), resulting in chyle leakage, which is a well‐known but poorly characterized complication of PD . This chyle leakage often presents as milky‐appearing drainage outflow, with a triglyceride content >110 mg/dL and usually becomes evident once oral or enteral feeding resumes after surgery . Chyle leakage might induce malnutrition and lead to an immune‐compromised state .…”
Section: Introductionmentioning
confidence: 99%
“…This chyle leakage often presents as milky‐appearing drainage outflow, with a triglyceride content >110 mg/dL and usually becomes evident once oral or enteral feeding resumes after surgery . Chyle leakage might induce malnutrition and lead to an immune‐compromised state . Available data on the incidence, risk factors, and clinical significance of chyle leakage are heterogeneous .…”
Section: Introductionmentioning
confidence: 99%
“…It could be in isolation as observed by us or in association with other common postpancreatectomy complications. Strobel et al, in their experience of 346 patients with chylous leak among 2881 patients undergoing pancreatic resection, reported an isolated chyle leak in 211 (11.1%) patients without concomitant intra‐abdominal complications and in the remaining 135 (13.8%) patients with other intra‐abdominal complications, that is, pancreatic fistula and intra‐abdominal abscess. van der Gaag et al pointed out that the surrounding inflammation and head mass with reactive lymph nodes induced by chronic pancreatitis require more extensive dissection, leading to chyle leak.…”
Section: Discussionmentioning
confidence: 99%
“…No patient required TPN or surgical treatment. Strobel et al managed 346 patients with chylous ascites with or without associated intra‐abdominal complications following pancreatic resection and concluded that all patients responded to combinations of MCT, TPN, and somatostatin. In our experience as well, all patients were successfully managed with customized enteral feeding of a high‐protein, low‐fat diet administered through a feeding jejunostomy or nasogastric tube along with supportive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Chyle leak is an important complication after pancreatic surgery which could be relevant to the present model because chyle contains triglycerides. Recently, chyle leak was found to be significantly associated with POPF. The major contents of chyle are not free triglycerides but chylomicron, which is a combination of lipoproteins and triglycerides, and pancreatic lipase cannot catalyse lipids within lipoproteins.…”
Section: Discussionmentioning
confidence: 99%